Analysis of Carbon Content in Dominant Macroalgae Types Found in Benoa Bay, Bali. - Siahainenia, Sheren Steffany; Dewi, Ayu Putu Wiweka Krisna; Saraswati, Ni Luh Gede Rai Ayu (Bumi Lestari; Vol 25 No 2 (2025), 2025)
Benoa Bay is a tidal water area. This tidal plain is a habitat for various types of flora and fauna diversity, one of which is macroalgae. Macroalgae are chlorophyll plants with a thallus-shaped morphological arrangement. This study aims to determine the types of macroalgae found in Benoa Bay, Bali, the percentage of macroalgae cover, macroalgae carbon content and water quality conditions. The method used in this research is quantitative descriptive method. Data collection procedures were carried out using simple random sampling techniques, namely observing directly in the field then calculating the percentage of cover, analyzing the amount of carbon that can be stored in macroalgae biomass, and measuring water quality. There were 15 species of macroalgae found in Benoa Bay, Bali. Macroalgae species that have high percentage cover values are found in 3 species, namely Ulva lactuca 49.62%; Gracilaria salicornia 9.67%; and Caulerpa cupressoides 5.15%. Carbon content measurements were carried out on dominant macroalgae, dominant species that have high percentage cover values. The carbon content in Ulva lactuca was 20.51%; Caulerpa cupressoides 16.99%; and Gracilaria Salicornia 4.68% with a stored carbon value of 41,322 g C/m², 56,183 g C/m²; and 4,191 g C/m², respectively. The results of water quality measurements on 7 parameters showed that Benoa Bay in optimal condition. This study shows that macroalgae in Benoa Bay, Bali has a good ability to absorb carbon in the waters.